Investigation on Efficient Removal of Fluoride from Ground Water Using Activated Carbon Adsorbents - Naga Dheeraj Kumar Reddy Chukka; P. Gomathi Nagajothi; L. Natrayan; Yeddula Bharath Simha Reddy; Dhinakaran Veeman; Pravin P. Patil; Subash Thanappan (Adsorption Science & Technology)
Groundwater seems to be the most significant natural source of potable water for millions of individuals. Fluoride pollution in groundwater is a big problem in Tamil Nadu’s Dharmapuri area. According to a survey done in a school in the Dharmapuri area, dental and skeletal fluoroses afflict almost 75% of school kids. There is no proven or recommended cost-effective strategy for lowering fluoride levels in the home. This study proposes cost-effective and efficient natural treatment approaches for lowering fluoride levels. In this experiment, fluorides in groundwater are eliminated to a suitable extent utilizing natural adsorbents. Neem stem charcoal (activated carbon), neem leaves powder, dry coconut husk, coconut shell charcoal (activated carbon), and rice husk powder are natural adsorbents. The adsorbents were utilized at different concentrations until the best concentration was found. The ideal concentration removes the bulk of fluoride from groundwater and delivers adequate treatment. People could adopt this cost-effective procedure because just a few components are enough. As per the Bureau of Indian Standards, the concentration should not exceed 1.5 ppm, and it should not be lesser than 1 ppm; keeping this in mind, the neem stem charcoal which has higher efficiency in removing fluoride can be used in extensive environments, but in this selected place, it reduces the concentration even below 1 ppm, which relays below the standard level. As a result, adopting these procedures helps prevent dental and skeletal fluoroses, which is common among young people.